An x-ray diffraction and Raman spectroscopy investigation of A-site substituted perovskite compounds: the (Na-1-K-x(x))(0.5)Bi0.5TiO3 (0 <= x <= 1) solid solution - Kreisel, J; Glazer, A; Jones, G; Thomas, P; Abello, L; Lucazeau, G (2000)
The (Na1-xKx)0.5Bi0.5TiO3 perovskite solid solution is investigated using x-ray diffraction (XRD) and Raman spectroscopy in order to follow the structural evolution between the end members Na0.5Bi0.5TiO3 (rhombohedral at 300 K) and K0.5Bi0.5TiO3 (tetragonal at 300 K). The Raman spectra are analysed with special regard to the hard modes and suggest the existence of nano-sized Bi3+TiO3 and (Na1-2xK2x)+TiO3 clusters. The complementary use of XRD and Raman spectroscopy suggests, in contrast to previous reported results, that the rhombohedral ↔ tetragonal phase transition goes through an intermediate phase, located at 0.5 ≤ x ≤ 0.80. The structural character of the intermediate phase is discussed in the light of sub- and super-group relations. © 2000 IOP Publishing Ltd.